(untitled) (BIS Humanities and Social Science, 2025)
This study examines the rebranding process of GRID Network, as part of Kompas-Gramedia (KG) media group, adapting digitally to this technology disruption. GRID network needs to cater technological and behavioral change in order to survive in this era, thus reimagining corporate branding in KG print media Group, is a necessity. Aims of this study is specifically to identify internal and external response to challenges during the rebranding of GRID Network and generally to assess the impact of digital transformation on brand equity and consumer loyalty within Indonesia’s magazine and tabloid case within a digitally interconnected society. This article attempts to focus on a single case-study through qualitative interviews with employees across management, comparing and confirming the branding and rebranding conceptual framework. The main findings show that GRID Network’s brand strategy, initially reactive to digital trends, may lack the strategic depth needed to build a unique identity, as it appears focused more on adapting to the interconnected, digital landscape than on establishing a cohesive brand image. This cautious entry into digital media may impact both employee alignment and consumer perception, with both groups potentially struggling to find relevance and consistency in the brand’s message. Recommendations include developing a unified brand identity that integrates core values, engages employees, and effectively bridges generational differences among consumers would help create a stronger brand presence and foster loyalty by aligning GRID Network’s digital transformation with clear, cohesive values that resonate across all audiences.